Multiplex Minisequencing of the HBB Gene: A Rapid Strategy to Confirm the Most Frequent β-Thalassemia Mutations in the Tunisian Population. (August 2015) - Ben Charfeddine, Ilhem; Ben Lazreg, Taheni; M'sakni, Ahlem; Amara, Abdelbasset; Mlika, Adnène; Chaïeb, Anouar; Hlel, Khalid; Zouari, Noura; Zbidi, Faïza; Bouguila, Jihène; Soyah, Najla; Ayedi, Abdelkarim; et al.
Abstract The β hemoglobinopathies [β-thalassemia (β-thal) and structural hemoglobin (Hb) variants such as Hb S (HBB: c.20A > T) and Hb E (HBB: c.79G > A)] are among the most common inherited diseases worldwide. In Tunisia, due to the high prevalence of consanguineous marriages, the recurrent risk of this disease is high. The average prevalence of hemoglobinopathies is 4.48%, reaching 12.50% in some focus regions. The molecular investigations on thalassemia contributed to establishing the spectrum of mutations in the Tunisian population. The total number of HBB gene mutations identified was 24. The two most frequent mutations, codon 39 (C > T) (HBB: c.118C > T) and IVS-I-110 (G > A) (HBB: c.93–21G > A) accounted for 70.0% of the total encountered β-thal cases. These two mutations together with IVS-I-2 (T > G) (HBB: c.92 + 2T > G) and the Hb S variant account for more than 90.0% of all HBB genetic variants in Tunisia. Thus, developing rapid, inexpensive and reliable mutation-specific molecular diagnostic assays targeting our Tunisian populations is our aim to facilitate routine detection of hemoglobinopathies. In this report, we describe the successful application of the multiplex minisequencing assay as an alternative strategy for genetic diagnosis of HBB gene disorders in Tunisia.